Valproic acid induces ferroptosis and suppresses the proliferation of MDA-MB-231 cells by targeting FDFT1 - Zhang, Shuxian; Liu, Jiazhuo; Yang, Yisong; Tao, Ran; Ren, Xin; Zhou, Xingzhi; Liu, Shuangping (Frontiers in Pharmacology, 2025)
IntroductionValproic acid (VPA) constitutes a branched-chain, short-chain fatty acid that serves as an antiepileptic medication. It has been increasingly recognized that VPA has presented potential anti-tumor properties, including breast cancer. However, the exploration of novel breast cancer treatment methods necessitates a more comprehensive and in-depth understanding of the novel mechanism of VPA inhibition of breast cancer. It has been proven that farnesyl-diphosphate farnesyltransferase 1 (FDFT1) participate in oncogenesis and development of cancers. However, the effect of FDFT1 on breast cancer is still obscure. Thus, it is important to investigate the potential of VPA to trigger ferroptosis in breast cancer cells via targeting FDFT1.MethodsIn this study, the underlying mechanisms of VPA on ferroptosis in breast cancer cells were explored in vitro and vivo. Initially, the effects of VPA on the proliferation of breast cancer cells were assessed utilizing the Cell Counting Kit-8, cell counting, and colony formation assays. Subsequently, the ferroptosis in breast cancer cells treated with VPA were determined through the use of the Lipid Peroxidation malondialdehyde Assay Kit, reduced glutathione and oxidized glutathione disulfide Assay Kit, flow cytometry, transmission electron microscopy, and western bloting. To explore the impact of VPA in combination with ferrostatin-1, Erastin or RSL3, on MDA-MB-231 cell proliferation and ferroptosis, respective CCK-8, colony formation and WB assays were conducted. Thereafter, we assessed whether VPA facilitated ferroptosis in MDA-MB-231 cells by modulating the expression of FDFT1. Finally, the anti-breast cancer effects of VPA in vivo were validated through a xenograft mouse model, and histological examination via hematoxylin-eosin staining and immunohistochemistry staining were employed to delve into the underlying mechanisms of VPA’s inhibitory effects on breast cancer cells in vivo.Results and DiscussionThe assay outcomes indicated that VPA impedes the proliferation of breast cancer cells. The findings from the ferroptosis index demonstrated that MDA-MB-231 cells are more sensitive to VPA induced ferroptosis than MCF-7 cells. Subsequent to the introduction of ferrostatin-1 (Fer-1), Erastin or RSL3, it was observed that Fer-1 reversed the ferroptosis facilitated by VPA, whereas Erastin or RSL3, in conjunction with VPA, respectively, induced ferroptosis in MDA-MB-231 cells. We revealed that the downregulation of FDFT1 enhanced proliferation and inhibited ferroptosis of MDA-MB-231 cells. Additionally, we discovered that VPA may facilitate ferroptosis in MDA-MB-231 cells by negatively modulating the levels of the solute carrier family 7 member 11 (SLC7A11) protein through the upregulation of FDFT1 expression. In conclusion, this study elucidated that VPA induced the ferroptosis of MDA-MB-231 cells via targeting FDFT1, representing a novel mechanism underlying its efficacy in potentially inhibiting breast cancer.